Understanding molecular crystal structures at extreme conditions - Funnell, Nicholas Paul (The University of Edinburgh, 2012)
Understanding the structure of matter in the solid state could be considered as being one of ‘the big questions’ in chemistry. Whereas the structural behaviour of molecules in the gas phase is relatively well-understood, this is not the case for the condensed phase due to the complexity of short and long-range intermolecular interactions. The purpose of the work in this thesis is to examine the structural response of solid molecular materials to stimuli of extreme pressure and temperature. L-alanine crystallises as a zwitterion in the space group P212121. Neutron powder diffraction and X-ray single crystal diffraction data show that the a and caxes are very similar in length. The a-axis is more compressible than the c-axis, and at ca. 2 GPa the cell becomes metrically tetragonal, however the underlying symmetry is still orthorhombic. The structure remains in a compressed form of the ambient phase up to 9.87 GPa. Previous Raman and energy dispersive powder diffraction studies have interpreted changes in spectra at ca. 2 and 9 GPa as phase transitions. The diffraction data and DFT calculations described here suggest that these are in fact due to changes in conformation of the ammonium group. L-alanine shows remarkable resistance to the effects of pressure but something must happen to the structure if pressure continues to be increased. Neutron powder diffraction has been used to obtain high-pressure data for L-alanine up to 15.46 GPa. These are the highest-pressure diffraction data reported for any amino acid. Above ca. 15 GPa, L-alanine undergoes a reversible transition to an amorphous phase through volume collapse of the crystal, driven by the need to minimise the PV term in the Gibbs free energy equation, as opposed to relieving destabilising contacts. It is currently the only amino acid known to undergo a transition of this type. The co-crystal of methylpyridine and pentachlorophenol (MP-PCP) forms in the space group P-1. When the phenolic proton is deuterated (MP-PCP-d) it exhibits isotopic polymorphism, crystallising in the space group Cc. Structures of the two other combinations of isotope and space group, i.e MP-PCP in Cc and MP-PCP-d in P-1 have not yet been determined. We demonstrate that these polymorphs can be obtained using high-pressure and low-temperature conditions predicted by thermodynamics. The use of in-situ crystallisation at pressure has driven MP-PCP to pack with Cc symmetry, minimising the PV term in the Gibbs free energy equation. Low-temperature crystallisation causes MP-PCP-d to form in P-1 due to this phase being favoured by vibrational enthalpic and entropic contributions. Aniline is a liquid under ambient conditions but freezes at 267 K in the monoclinic space group P21/c. It can also be frozen by pressure (ca. 0.8 GPa) in the orthorhombic space group Pna21. Neutron powder diffraction shows that on decompression the orthorhombic form transforms to the monoclinic phase at 0.3 GPa, owing to the monoclinic packing being less dense. PIXEL calculations provide an insight into the intermolecular energies of the orthorhombic crystal up to 7.301 GPa. They show that dispersive forces are more dominant than the hydrogen bonds, one of which becomes destabilising at higher pressure. Thermodynamic calculations estimating the relative stabilities of the two polymorphs prove inconclusive owing to improper treatment of dispersion interactions by Density Functional Theory calculations. The structural behaviour of cyclohexane in the crystalline (P21/c) and plastic phases (Fm3m) has been studied using neutron total scattering data and Reverse Monte Carlo (RMC) modelling. Atomistic models show that the molecules exhibit correlated motion as they prepare to undergo transformation on heating. Inclusion of I(t) data in the RMC refinements is shown to be important as when it is not accounted for, the RMC method is incapable of distinguishing the form of the disorder in the plastic phase. Molecular motion in this phase is shown to be correlated through the avoidance of short intermolecular D···D contacts. The ordered and disordered solid phases of oxalyl chloride (space groups P21/c and Pbca respectively) have been studied by neutron total scattering and modelled using a Reverse Monte Carlo approach. Atomistic models show that on heating, the atoms vibrate out of the plane of the molecule until 245 K where they show approximately isotropic vibration owing to reduced steric restriction. This may provide the molecules with the freedom they require to rotate and undergo the solidsolid transition. The onset of disorder has also been partially predicted by molecular dynamics simulations. RMC modelling does not provide satisfactory atomic configurations of the disordered solid phase due to an unrealistic distribution of intermolecular chlorine-chlorine contacts. This study presents an example of a flexible, 3-atom-type system that may be too complex for analysis by the RMC method.
Keywords: high-pressure; x-ray; neutron; crystallography; total scattering; polymorph; phase transition